Depression, professional self-efficacy, and job performance as predictors of life satisfaction: the mediating role of work engagement in nurses - Morales-García, Wilter C.; Vallejos, María; Sairitupa-Sanchez, Liset Z.; Morales-García, Sandra B.; Rivera-Lozada, Oriana; Morales-García, Mardel (Frontiers in Public Health, 2024)
Background The life satisfaction and job performance of nursing professionals are affected by a multitude of factors, including work engagement, self-efficacy, and depression. The Job Demands-Resources (JD-R) model provides a theoretical framework to explore these relationships. Objective Our study aimed to analyze the primary goal of this research, which is to examine the mediating role of work engagement in the relationship between depression, professional self-efficacy, job performance, and their impact on life satisfaction in nurses, using the JD-R theory as a guide. Methods This cross-sectional study involved 579 participants aged between 21 to 57 years (M = 39, SD = 9.95). Mediation analysis was used to examine the influence of depression, self-efficacy, and job performance on work engagement, and in turn, its effect on life satisfaction. Results Findings indicated that work engagement plays a crucial mediating role between depression, self-efficacy, job performance, and life satisfaction. Interventions to increase work engagement could assist nurses in better managing depression and improving their performance and life satisfaction. Conclusions Our study highlights the need for workplace policies and strategies that foster work engagement and self-efficacy among nurses while effectively managing job demands to prevent depression. Moreover, these findings underscore the importance of the JD-R theory to understand and improve nurses' job satisfaction and performance, and suggest areas for future research, including exploring other potential factors and applying these findings across different contexts and cultures.